Second Language Acquisition and Educational Technology: Trends and Challenges in English Learning - Yadav, Aditya Kumar (Journal of Advanced Research in English & Education; Vol 9 No 3 (2024): Journal of Advanced Research in English & Education, 2024)
Second Language Acquisition (SLA) has seen significant advancements with the integration of educational technology, which offers innovative tools to enhance language learning. This review explores the current trends in SLA and educational technology, focusing on how digital resources, AI-driven platforms, and mobile learning are shaping English language education. Advances in technology have revolutionized how second languages are taught, providing learners with opportunities for increased interaction, personalized instruction, and greater access to diverse learning materials. However, while these advancements provide numerous benefits, challenges such as access disparities, technological overload, and privacy concerns persist. Limited access to reliable internet and digital devices, the overwhelming number of technological tools available, and concerns about the security and ethical use of learner data remain significant barriers to effective implementation. This article discusses both the opportunities and obstacles, offering insights into future directions for the integration of technology in SLA, aimed at fostering effective, inclusive, and personalized learning experiences. By addressing these challenges through innovative approaches and interdisciplinary research, educators and technologists can create more accessible, engaging, and impactful language learning environments.